Endodontic Management of a Fused Mandibular Second Molar and Paramolar: A Case Report - Salem Milani, Amin (Iranian Endodontic Journal, 2010)
Tooth fusion is a developmental anomaly characterized by the union between the dentin and/or enamel of at least two separately developing teeth. The fusion of posterior teeth is an uncommon occurrence. In this article, we report a rare case of unilateral fusion of a mandibular second molar with a paramolar. Carious exposure mandated endodontic treatment. The unusual morphology and complex root canal system makes diagnosis and treatment difficult. In this case, successful endodontic management was carried out with precise application of hand and rotary techniques.